If women are everywhere: tracing the multiplicity of women's resistance to extraction in NSW, Australia. Issue 3 (4th March 2021) - Ey, Melina
Abstract: In response to the longstanding erasure of women from representations of resistance within the academy, increasing attention is being paid to myriad ways in which women are performing and enacting resistance. This is particularly evident in burgeoning research exploring women's resistance to natural resource extraction. However, within this literature, a prevailing reliance on gender as an explanatory analytic runs the risk of overlooking a much wider, messier and diverse resistance terrain. This paper argues that in continuing to rely primarily on gender to frame and analyse women's resistance to resource extraction, gender can inadvertently become installed as a form of strong theory, which obscures the many ways in which women's resistance to natural resource extraction is multiple, contingent, more-than-gendered, and more-than-human. Rather than relying on singular categories of social difference (such as gender) to explain women's resistance, this paper turns to weak theory to move away from explaining why women resist, to instead exploring the many diverse ways that they resist. Drawing on two stories of women's resistance to natural resource extraction in New South Wales, Australia, this paper uses weak theory to attend to the diverse more-than-gendered and more-than-human ways in which women resist, and argues that such multiplicity is erased when women's resistance to resource extraction continues to be approached primarily through singular analytical framings.